Group High Risk of HIV in Central African Republic : Classification and arly Intervention - (:unkn) unknown (My University, 2016)
Keywords : high risk group- typology - FSW - MSM –HIV -STD- Central AfricanBackground: The population of female sex workers (FSW) and the group of men who have sex with men (MSM) constitutes a priori an important core group of HIV transmission. In the context of the Central African Republic the situation of FSW and MSM is yet unknown. The objectives of this thesis were to establish a documented typology of female sexual transactions in Bangui and to measure the prevalence of HIV and associated comorbidities in these two populations.Materials and Methods: First 1384 sensitized female volunteers were recruited to the site of their activities and oriented at the survey site. Finally, 345 FSW questionnaires were selected for study analysis. MSM were recruited on a voluntary basis by the way of local network of nonprofit organizations working in the field of HIV infection. Included MSM were referred to the National STD center of Bangui for social, behavioral and medical evaluation. After collection of social and behavioral characteristics, each participant received a physical examination and a blood sample was taken for HIV and STD testing.Main results: Female prostitution in the CAR is remarkably heterogeneous. Risk-taking regarding HIV infection is very different between each category of female prostitution. HIV varied according to FSW categories, Thus, HIV prevalence was 6-fold higher among « kata » than « pupulenge » (39.1% versus 6.3%).Among non professionnal FSW, « students », « civil servants » and « housewifes » were the less infected (6.1%, 9.8%, 13.0%, respectively), whereas « sellers » constituted the category of highest HIV prevalence (31.9%).HIV infection in the whole study FSW population was strongly associated with anal sex practice with last clients (adjusted OR, 4.3), condom use in last 3 months (adjusted OR, 24.9), alcohol consumption before sex (adjusted OR, 2.8) and past history of STIs (adjusted OR, 4.2). The population of
Keywords: African Research